The Age and Time of Screenagers: A Sneak-Peek into the Paradigm Shift in English Language Teaching and Learning in the Indian Educational Landscape - Thosar, Ashwini (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
The name "Screenagers" combines the words "screen" and "teenagers," and it refers to young people and their fixation with screens. In the context of this study article, this phrase refers to the use of technology tools for English language learning. The world has been a witness to numerous technological advancements and they have paved their way into the educational sector as well. Considering the advancement of technology in education, a change from the conventional chalk-and-blackboard teaching style to the online teaching approach in language teaching has been observed. These changes took place gradually, beginning with the advent of CALL (Computer-Assisted Language Learning), commonly known as the ICT era, and continuing with WELL (Web-Enhanced Language Learning), followed by MALL (Mobile-Assisted Language Learning), and so on. As a result of these advancements, language learning is aided by technological resources. This change has not only made it possible for learners to participate more actively but has also provided teachers the ability to implement the blended learning strategy in the classroom. Since technology has a significant impact on Gen-Z learners and can be used to engage students in active learning while maintaining high standards for instruction and learning outcomes, there are many benefits to integrating it into classroom teaching and learning.